Techniques for Reading Number Notation and Musical Elements for Singers at Gki Martin Luther Sentani: Teknik Membaca Notasi Angka Dan Unsur Musik Bagi Singers Di Gki Martin Luther Sentani - Sahureka, Cosye Meilina (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
This study examines the use of number notation as a practical tool for reading musical chords, focusing on its application by singers during preparation for worship performances. The structural foundation of music—comprising melody, harmony, rhythm, and dynamics—serves as a basis for understanding and interpreting musical pieces. Combining this foundation with number notation facilitates high-quality and expressive musical performances by vocalists and instrumentalists. The study employs a descriptive qualitative method, with data collected through observations and interviews with singers at GKI Martin Luther Sentani. The findings reveal that singers have incorporated number notation techniques during independent practice sessions to enhance their readiness for Sunday worship performances. While the application is not yet perfect, these techniques have significantly contributed to their preparation. Key techniques include acquiring basic knowledge of number notation, practicing mindfulness in singing, using online tutorials for guidance, collaborating with peers during practice, and maintaining consistency in rehearsal routines. The study underscores the importance of number notation as a foundational tool for singers to improve their performance quality. It highlights how structured and consistent practice can aid in mastering the notation and enhance musical expression in worship contexts. These findings provide valuable insights for music educators and church communities seeking to optimize preparation and performance processes in similar settings.